TBP loading by AF4 through SL1 is the major rate-limiting step in MLL fusion-dependent transcription. Issue 20 (17th October 2016) - Okuda, Hiroshi; Takahashi, Satoshi; Takaori-Kondo, Akifumi; Yokoyama, Akihiko
ABSTRACT: Gene rearrangement of the mixed lineage leukemia ( MLL ) gene causes leukemia by inducing the constitutive expression of a gene subset normally expressed only in the immature haematopoietic progenitor cells. MLL gene rearrangements often generate fusion products of MLL and a component of the AF4 family/ENL family/P-TEFb (AEP) complex. MLL-AEP fusion proteins have the potential of constitutively recruiting the P-TEFb elongation complex. Thus, it is hypothesized that relieving the promoter proximal pausing of RNA polymerase II is the rate-limiting step of MLL fusion-dependent transcription. AEP also has the potential to recruit the mediator complex via MED26. We recently showed that AEP activates transcription initiation by facilitating TBP loading to the TATA element through the SL1 complex. In the present study, we show that the key activity responsible for the oncogenic property of MLL-AEP fusion proteins is the TBP loading activity, and not the mediator recruitment or transcriptional elongation activities. Thus, we propose that TBP loading by AF4 through SL1 is the major rate-limiting step in MLL fusion-dependent transcription.